MANAJEMEN PRODUKSI STICK KEJU PADA HOME INDUSTRY EFRATA STICK KEJU DI BANDAR LAMPUNG - Marvin, Jesslyn Angelica; Hepiana Patmarina (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Production management is a decision-making process in a company to produce a product effectively and efficiently. Good production management can be achieved when the implementation of all management functions goes well without any problems. The purpose of this research is to find out the implementation of actuating function and controlling function in the production management of Home Industry Efrata Stick Keju. Data collection techniques in this research are observation, interview, and documentation. The Informant in this research is the leader and also owner of Home Industry Efrata Stick Keju. The data analysis technique used in this research is the qualitative data analysis technique of Miles and Huberman model. The results of this research show that the production management of Home Industry Efrata Stick Keju is not optimal because the implementation of actuating function and controlling function have not been carried out properly. Keywords: Home Industry, Management, Production